The effect of taxation knowledge, fairness and leadership style on tax compliance with organizational culture as a moderating variable on MSME corporate taxpayers in Bandung City - Rahmawati, Eko; Silviana, Silviana (Educoretax, 2025)
Tax is a social contract between citizens and the government, both parties are expected to uphold their mutual responsibilities. Citizens are expected to pay their taxes, and the government is supposed to use the tax proceeds for the welfare and benefit of the citizens. In reality, no one likes to pay taxes, therefore it is necessary to study the factors that can make people obedient to taxes. Taxpayer compliance behavior is not only influenced by economic factors but also non-economic factors such as tax knowledge, the perception of tax fairness, leadership style, and organizational culture. This study aims to analyze the influence of Tax Knowledge, Fairness Principles, and Leadership Style on Tax Compliance of corporate MSME taxpayers in Bandung and to examine the role of Organizational Culture as a moderating variable. The study uses a quantitative approach with primary data sources collected through a survey method. The sample consists of 163 respondents, selected using purposive sampling, who represent corporate MSME taxpayers in Bandung. Data analysis was performed using multiple linear regression and moderation regression analysis (MRA) using SPSS Statistic 26. The results showed that Tax Knowledge has a significant and positive effect on Tax Compliance, the Fairness Principle has a significant effect, Leadership Style has a significant positive effect on tax compliance, Organizational Culture weakens the influence of tax knowledge on tax compliance, but strengthens the influence of the Principle of Fairness on tax compliance. However Organizational Culture is unable to moderate the influence of Leadership Style on Tax Compliance.